Family violence from a global perspective : a strengths-based approach - Asay, Sylvia M.; DeFrain, John D.; Metzger, Marcee; Moyer, Bob (Los Angeles : SAGE, 2014)
Drawing on the expertise of authors from 21 countries to tell the story of domestic violence in their country, it lends academic, professional, and victims' expertise to determine these strengths and analyze how they can translate into greater safety for victims and increased accountability for perpetrators, including imroved policy formation.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Family violence -- Case studies